How ions arrange in solution: detailed insight from NMR spectroscopy of paramagnetic ion pairs - Damjanović, Marko; Morita, Takaumi; Horii, Yoji; Katoh, Keiichi; Yamashita, Masahiro; Enders, Markus (ChemPhysChem, 2016)
Abstract Ion pairing between the paramagnetic anion [Tb(obPc)2]? (obPc=2,3,9,10,16,17,23,24-octabutoxyphthalocyaninato), which has a very large magnetic anisotropy, with various diamagnetic counterions [P(Ph)4]+ (1?a), [As(Ph)4]+ (1?b), bis(triphenylphosphine)iminium ([PPN]+, 1?c) and tetra-n-butylammonium ([TBA]+, 1?d) was studied by means of 1H, 13C, 14N, and 31P?NMR spectroscopy in solution at various temperatures. The influence of the paramagnetic anion on the NMR spectroscopy properties of the diamagnetic cations allowed a detailed insight into the distances and relative orientations of the paired ions. Isotropic tumbling models for the description of the quaternary cations are inaccurate, particularly for [TBA]+ with its flexible butyl chains. The effects of temperature and concentration were also assessed. The advantage of this technique is that relatively large distances and the orientation between molecules or ions in solution can be studied.